Mistitisme Islam Prof. Dr. H. Nurcholis Madjid - Muhajirin, Muhajirin; Mahmuddin, Mahmuddin; Santalia, Indo (Lembaga Penelitian dan Pengabdian kepada Masyarakat (Center for Research and Community Services), Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
This study explores the concept of Islamic mysticism (tasawwuf) as conceptualized and advocated by Prof. Dr. H. Nurcholish Madjid, a renowned Indonesian Muslim intellectual. The research aims to examine how Madjid understands mysticism not merely as a path of personal spirituality, but as a transformative force that integrates inner piety with social ethics. Using a qualitative-descriptive approach, this study analyzes Madjid’s key writings and public lectures, particularly his interpretation of central Sufi concepts such as tazkiyah al-nafs (self-purification), ma'rifah (gnosis), and tawḥīd (the oneness of God) within the context of contemporary Indonesian Islam. The findings reveal that Madjid’s approach to mysticism is inclusive, rational, and reformist—emphasizing inner transformation while reinforcing its relevance to social renewal, ethical consciousness, and democratic values. His mystical thought presents an integrative paradigm in which spiritual depth and intellectual engagement coexist, contributing to the development of a more tolerant, ethical, and pluralistic Islamic society. This study affirms the contemporary relevance of Islamic mysticism in shaping religious discourse, ethical leadership, and civic participation in Indonesia.